Problems of Valuation Activity in The Conditions of Development of Agricultural Market Relations Republic (Eurasian Research Bulletin, 2024)
This article examines foreign experience in the development of agriculture and factors influencing the development of agricultural activities, work carried out in this direction in our country in subsequent years. Areas of legislation adopted in our country were also touched upon